General problems encountered by the postgraduate first-time electron microscopist - Grossman, E. S. (My University, 1988)
This article identifies the main problems encountered by the postgraduate first- time electron microscopist. Areas where difficulties arise occurred in the communication and planning of the project, general specimen preparation, safety in the laboratory, and in the use of the electron microscope facility. It is recommended that all students who wish to use the electron microscope as a research tool should attend a short course in EM organised by the EM unit staff in conjunction with the various academic departments whose students make use of the facility, before embarking on their research topic.
PK
Keywords: Microscopy, Electron